Effect of evolution of polycrystalline textures on r-value of LF2 aluminum alloy - 赵亦希 林忠钦 李淑慧 于忠奇 (Transactions of Nonferrous Metals Society of China, 2006)
The effect of evolution of polycrystalline texture on normal anisotropy coefficient r-value of aluminum alloy sheet was investigated. For this purpose, the textures under different elongation of LF2 aluminum alloy were measured and analyzed. The result indicates that the initial texture of LF2 aluminum alloy has the typical rolling texture, and the main components include Brass {011 } （2H）, Copper { 112}（111）and S{ 123}（634）. These three main components exhibit different transformation tendencies when the material specimens are stretched along the different direction. Based on Taylor model and Minor Work principle, the normal anisotropy coefficient r-values ofpolycrystalline aluminum alloy under various strain states were calculated. The result indicates that the r-values of LF2 aluminum alloy vary with tensile direction and the amount of deformation. The deformability on rolling direction is superior to the other direction because an enhancement tendency of r0 appears in tension process along rolling direction.